Information Internalization and Hurdle Rates in Small and Medium Enterprise Internationalization - Liesch, Peter W.; Knight, Gary A. (Journal of International Business Studies, 1999)
We investigate the role of information in the internationalization of small and medium enterprises (SMEs). Information internalization is fundamentally antecedent to SME internationalization and is being facilitated increasingly by recent important trends. We offer a conceptual explanation and related propositions on information internalization, emphasizing hurdle rate theory for ascertaining the acceptability of firms' internationalization projects.